Psychometric Properties of the Weekly Assessment of Child Behavior–Positive Form (WACB-P). (December 2021) - Timmer, Susan Goff; Usacheva, Maria; Maise, Amanda Ayers; Hutchison, Shari L.; Armendariz, Lindsay F.; Herschell, Amy D.
Using measurement-based and feedback-informed approaches is key to providing effective family-centered clinical care; a strength-based approach is shown to improve treatment outcomes and satisfaction. Yet, there are few brief, psychometrically sound assessment tools for preschool-age and elementary school–age children. In response, we developed a nine-item, two-scale measure, the Weekly Assessment of Child Behavior–Positive (WACB-P), suitable for children ages 2 to 12 years. We examined the psychometric properties of the WACB-P based on two low-income clinical samples differing in intervention modality and location (Sample 1: N = 285; Sample 2: N = 137). WACB-P demonstrated high internal validity and test–retest reliability. The item response theory (IRT) paradigm applied to the Intensity Scale revealed that the items showed moderate discrimination and adequate precision, particularly effectively capturing behavioral challenges. Repeated-measures analysis of covariance (RM-ANCOVA) showed significant linear effects from session to session, suggesting sensitivity to change during treatment. WACB-P demonstrated strong convergent validity with established measures of child behavior problems. These favorable results position the WACB-P as a suitable choice for agencies providing measurement-based behavioral health care for young children and their families.